2022
DOI: 10.3390/antibiotics11040494
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mutations in DNA Gyrase and Topoisomerase IV in Field Strains and In Vitro Selected Quinolone-Resistant Mycoplasma hyorhinis Mutants

Abstract: Mycoplasma hyorhinis is ubiquitous in swine, and it is a common pathogen of swine that causes polyserositis, arthritis, and maybe pneumonia. Fluoroquinolones are effective antimicrobials used for the treatment of mycoplasmal infection. However, a decrease in fluoroquinolones susceptibility in mycoplasma was observed. The molecular mechanisms have been studied in many mycoplasma species, while the mechanism in M. hyorhinis is still unknown. This study aimed to illustrate the in vitro development of fluoroquinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…For example, the bacterial topoisomerases DNA gyrase GyrB is an essential enzyme that controls the topological state of DNA during replication (Tari et al, 2013). Previous studies reported the important role of GyrB in bacterial fluoroquinolone resistance (Chauffour et al, 2021; Li et al, 2022). The 3D structure prediction showed that GyrB K331 is located in the ATPase domain that is responsible for supercoiling DNA, whereas K449 is located in the Toprim domain that is required for the interaction with GyrA (Brino et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the bacterial topoisomerases DNA gyrase GyrB is an essential enzyme that controls the topological state of DNA during replication (Tari et al, 2013). Previous studies reported the important role of GyrB in bacterial fluoroquinolone resistance (Chauffour et al, 2021; Li et al, 2022). The 3D structure prediction showed that GyrB K331 is located in the ATPase domain that is responsible for supercoiling DNA, whereas K449 is located in the Toprim domain that is required for the interaction with GyrA (Brino et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, substitutions at positions 80 and 84 in the topoisomerase IV ( parC ) gene were found to be significant for resistance to fluoroquinolones [ 25 ]. These codon substitutions were not detected in all our sequences that have been analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Since mycoplasmas are generally very demanding concerning their culture conditions, it is necessary to accept certain difficulties, such as expensive or very complex broth media as well as the extended growth periods, also for AST methods. Several very different agar and broth media have been used over time for AST of porcine mycoplasmas: Friis media [6,8,9,25], modified Friis media [15,25,37], the commercial Liquid Mycoplasma Medium (Mycoplasma Experience Ltd., UK) [19,20,38], variations of YUS and CMRL media [30], M media [14,36,39] and KM2 media [40]. According to the published literature, for M. hyorhinis and M. hyopneumoniae, the (modified) Friis broth appears to be the most reliable culture medium so far.…”
Section: Antimicrobial Susceptibility Testing Of M Hyorhinis Field Is...mentioning
confidence: 99%
“…Although the AST methodology previously used was different between working groups, most still agree on using the type strain of M. hyorhinis as a reference and for quality control purposes without generally valid quality control ranges [8,9,[14][15][16]19,25,36,37,40]. Due to the variety of broth media used in broth microdilution methods, the resulting MIC values might differ as well.…”
Section: Antimicrobial Susceptibility Testing Of M Hyorhinis Field Is...mentioning
confidence: 99%
See 1 more Smart Citation